Effect of probiotic therapy on periodontal tissues and intestinal mucosa of rats with ligature-induced periodontitis - Rodrigues, Pedro Henrique de Carli (2023)
Introduction: As periodontitis is caused by dysbiotic biofilm, it is believed that therapy with probiotics can act to control the mechanisms of adhesion and colonization, competing with invading microorganisms. Objective: Evaluate probiotic therapy effect on periodontal tissues and intestinal mucosa of rats with ligature-induced periodontitis. Methods: 32 Wistar rats were divided into four groups (n=8): Control Group (CG); Periodontal disease (PD); Probiotic (PROB); PD + probiotic (PDPRO). PD and PDPRO received a ligature over the first lower molars and PROB and PDPRO the probiotic Lactobacillus acidophilus based were given orally for 44 days. The animals were euthanized and the blood was collected for evaluation of triglyceride and cholesterol concentrations. The hemimandibles were collected for histomorphometric and radiographic analysis. The duodenum was removed for morphological evaluation and gingival tissue around the molars was collected for analysis of IL-17. Results: The ANOVA one-way test was used followed by Tukey Test. PDPRO had a significantly lower bone loss than the PD (p<0.05) and a smaller number of osteoclasts on PDPRO when compared to the PD. As for IL-17, there was a decrease in the PDPRO when compared to the PD. The histomorphometry of the duodenum showed that there was a significant increase in the width of the villi in PROB only. Conclusion: The therapy with probiotics was effective to avoid the development of periodontitis by reducing alveolar bone loss and inflammation modulation and increasing the width of the duodenum villi, which may help to restabilize the balance of the gastrointestinal tract.